2010
DOI: 10.1111/j.1600-0625.2010.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the IL-2-inducible tyrosine kinase (Itk) activity: a new concept for the therapy of inflammatory skin diseases

Abstract: T-cell-mediated processes play an essential role in the pathogenesis of several inflammatory skin diseases such as atopic dermatitis, allergic contact dermatitis and psoriasis. The aim of this study was to investigate the role of the IL-2-inducible tyrosine kinase (Itk), an enzyme acting downstream of the T-cell receptor (TCR), in T-cell-dependent skin inflammation using three approaches. Itk knockout mice display significantly reduced inflammatory symptoms in mouse models of acute and subacute contact hyperse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Itk −/− mice show reduced levels of IL-4 and IL-13 but not IFNγ (mRNA and protein) as measured in the lungs of Itk knockout mice compared to wild type mice (WT) [27], [28] and this effect was accompanied by a significant reduction in the Th2 promoting transcription factor GATA3 [27]. Furthermore, Itk −/− mice showed a reduced response in a model of atopic dermatitis [29]. In human studies, genetic analysis has shown SNPs in Itk are associated with atopy, allergic rhinitis and asthma [30], [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Itk −/− mice show reduced levels of IL-4 and IL-13 but not IFNγ (mRNA and protein) as measured in the lungs of Itk knockout mice compared to wild type mice (WT) [27], [28] and this effect was accompanied by a significant reduction in the Th2 promoting transcription factor GATA3 [27]. Furthermore, Itk −/− mice showed a reduced response in a model of atopic dermatitis [29]. In human studies, genetic analysis has shown SNPs in Itk are associated with atopy, allergic rhinitis and asthma [30], [31].…”
Section: Discussionmentioning
confidence: 99%
“…ITK mRNA levels in the peripheral blood T cells is elevated in atopic dermatitis patients compared to healthy controls, and this increase correlates with disease severity [44]. Furthermore, ITK expression is increased in lesional skin from patients with atopic dermatitis and allergic contact dermatitis [29]. Itk −/− mice show significantly reduced inflammation in models of contact hypersensitivity, and this anti-inflammatory effect was reproduced by systemic administration of an ITK inhibitor [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a few mediators of T H 9 driven inflammation in atopic dermatitis have been identified. For instance, Itk, a mediator of T cell receptor signaling and a positive regulator of T H 9 differentiation has been shown to be expressed in T cells in lesional skin of AD but not in psoriasis [48, 49]. As for the downstream effects of IL-9 in atopic dermatitis, similar considerations can be made as have been outlined above for their role in skin infection (Fig.…”
Section: Th9 Cells In Skin Disordersmentioning
confidence: 97%
“…Itk plays an important role in transmitting signals at the immunological synapse, Itk (Ϫ/Ϫ) cells had severe reduction of IL-2 and IFN-␥ secretion (Schaeffer et al, 1999;von Bonin et al, 2011). After incubation of Jurkat cells with 0.5 M CTA056, the mRNA levels of IL-2 and IFN-␥ were measured using real-time PCR, and the IL-2 and IFN-␥ secretions were measured using an ELISA assay.…”
Section: Cta056 Inhibits the Formation Of Phospho-itk In Jurkat Cellsmentioning
confidence: 99%